(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
This research aims to study the biodiversity of benthic macroalgae and determine their abundance on the northern and southern shores of the city of Jableh. The study site was divided into two regions (northern and southern), and each site was divided into three sampling stations from different points. Samples were collected from depths (0.5 - 1) m during the spring months of 2021, the period of maximum growth of benthic algae. The spread and abundance of species at the three study stations for each of the two study sites differed depending on the nature of the bottom, the movement of water and nutrients, and the concentration of pollution from household waste and sewage was the main factor. 35 Species of benthic algae were identifid at the first site, While the number of species in the second site reached 32 species. The abundance of both types green algae species (Enteromorpha, Ulva) was observed in station water polluted with sewage, while the abundance of Brown (Sargassum) and Red algae (Pterocladia) increased in less polluted water.